2023
DOI: 10.1111/dom.14987
|View full text |Cite
|
Sign up to set email alerts
|

Integrated safety and efficacy analysis of dasiglucagon for the treatment of severe hypoglycaemia in individuals with type 1 diabetes

Abstract: Aims:To perform an integrated analysis of the safety and efficacy of dasiglucagon, a glucagon analogue available in a ready-to-use aqueous formulation, to treat severe hypoglycaemia (SH) in type 1 diabetes (T1D).Materials and Methods: An integrated analysis of dasiglucagon safety was conducted on data from two placebo-controlled trials (placebo-controlled pool) and two placebo-controlled and four non-placebo-controlled trials (broad pool) in adults with T1D. An integrated analysis of dasiglucagon efficacy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…Glucagon is highly efficacious for the primary treatment of severe hypoglycemia when a patient is unable to ingest carbohydrate safely, but it is unfortunately under-prescribed and underused 131132. Availability of nasal, ready to inject, and shelf-stable liquid glucagon formulations have superseded the need for reconstituting older injectable glucagon preparations before administration and are now preferred 133134. Real time CGM studies have shown a decreased hypoglycemic exposure in people with impaired awareness without a change in HbA 1c 34135136137138.…”
Section: Updates In Acute Complications Of Type 1 Diabetesmentioning
confidence: 99%
“…Glucagon is highly efficacious for the primary treatment of severe hypoglycemia when a patient is unable to ingest carbohydrate safely, but it is unfortunately under-prescribed and underused 131132. Availability of nasal, ready to inject, and shelf-stable liquid glucagon formulations have superseded the need for reconstituting older injectable glucagon preparations before administration and are now preferred 133134. Real time CGM studies have shown a decreased hypoglycemic exposure in people with impaired awareness without a change in HbA 1c 34135136137138.…”
Section: Updates In Acute Complications Of Type 1 Diabetesmentioning
confidence: 99%